Aligning the Audit Themes with Government Priority to Improve the Effectiveness of Performance Audit (Case Study in Supreme Audit Institution in Indonesia) - Wibisono, Windhu; V. Salomo, Roy; Wijaya, Chandra (International Journal of Engineering and Technology, 2018)
Various implementations of public policies in democratic countries need the oversight from external to obtain the public trust and policy legitimacy of the government policy itself. Indonesiaâ€™s government needs to improve the quality of the evaluation, including policy evaluation from the external, in this case is the Supreme Audit Institution (SAI). This paper will describes how the performance audit role of the SAI according to the constitution, the mindset about performance audits from informants, and how to answer the mindset regarding a performance audit that closer to management. This paper uses qualitative approach based on in-depth interviews with SAIâ€™s officials and the secondary data. This paper describes perspectives from SAIâ€™s internal and external about the focus of performance audit. Many perspectives brought to describes how the SAI use alignment strategy that linier with government strategy in a medium term development plan. This paper concludes that SAIâ€™s performance audit can be regarded as a good baseline in the policy evaluation if it aligns with the government strategy as declared in RPJMN. This suggests an indication of democratic governance of BPK performance audit at least from the input stage or audit-planning phase.Â Â